Josephus Daniels : His Life and Times - Craig, Lee A. (Lee Allan), 1960- (Book collections on Project MUSE., 2013)
"As a longtime leader of the Democratic Party and key member of Woodrow Wilson's cabinet, Josephus Daniels was one of the most influential progressive politicians in the country, and as secretary of the navy during the First World War, he became one of the most important men in the world. Before that, Daniels revolutionized the newspaper industry in the South, forever changing the relationship between politics and the news media. Lee A. Craig, an expert on economic history, delves into Daniels's extensive archive to inform this nuanced and eminently readable biography, following Daniels's rise to power in North Carolina and chronicling his influence on twentieth-century politics"--